High post-treatment platelet reactivity is associated with a high incidence of myonecrosis after stenting for non-ST elevation acute coronary syndromes - Cuisset, Thomas; Frere, Corinne; Quilici, Jacques; Morange, Pierre-Emmanuel; Nait-Saidi, Lyassine; Mielot, Christopher; Bali, Laurent; Lambert, Marc; Alessi, Marie-Christine; Bonnet, Jean-Louis (Thrombosis and Haemostasis, 2007)
High post-treatment platelet reactivity (HPPR= adenosine diphosphate [ADP] 10 µM-induced platelet aggregation > 70%) identifies low responders to dual antiplatelet therapy with increased risk of recurrent cardiovascular (CV) events after stenting for non-ST elevation acute coronary syndromes (NSTEACS). This study was designed to compare the incidence of periprocedural myocardial infarction (MI) after stenting for NSTEACS patients between non-responders to dual antiplatelet therapy defined by HPPR and normo-responders. One hundred ninety NSTE-ACS consecutive patients undergoing coronary stenting were included in this prospective study. They received 250 mg aspirin and a 600 mg loading dose of clopidogrel at least 12 hours (h) before percutaneous coronary intervention (PCI). A single post-treatment blood sample was obtained before PCI to analyze maximal intensity of ADP-induced platelet aggregation, and troponin levels were analyzed before PCI, and 12 and 24 h after PCI. Troponin I was considered elevated if > 0.4 ng/ ml. HPPR was present in 22% of patients (n=42). Periprocedural MI occurred significantly more frequently in patients with HPPR than in the normo-responders (43% vs. 24%, p=0.014). After being correlated with recurrent ischemic events after stenting for NSTE-ACS, the HPPR seems to be also a marker of increased risk of periprocedural MI for NSTE-ACS patients.
Keywords: Acute coronary syndromes; stenting; platelet reactivity; periprocedural myocardial infarction